Augmented Reality sebagai Media Pembelajaran pada Pengenalan Komponen Dasar Elektronika Berbasis Android - Suci Ramadhani; Ervan Asri; Taufik Gusman (SOTVI - Society of Visual Informatics, 2021)
The learning process or other activities related to electronics are often faced with various symbols of electronic components, where sometimes it is difficult to distinguish and know the symbols, physical forms, and functions of these electronic components. Especially at this time the learning process is carried out online. So that students do not understand the material being taught. For this reason, it is necessary to make learning media using augmented reality technology to make it easier for students to learn about basic electronic components. The system is built using the android platform that displays 3D models using markers in the form of 2D images and presents an interface and 3D image processing for basic electronics components using Unity 3D software. The programming line used is C#, the augmented reality technology processing engine used in this application is Vuforia which is an additional package to the Unity 3D Software